Coronary artery calcification outperforms thoracic aortic calcification for the prediction of myocardial infarction and all-cause mortality: The Heinz Nixdorf Recall Study. (September 2014) - Kälsch, Hagen; Lehmann, Nils; Berg, Marie H; Mahabadi, Amir A; Mergen, Paul; Möhlenkamp, Stefan; Bauer, Marcus; Kara, Kaffer; Dragano, Nico; Hoffmann, Barbara; Moebus, Susanne; Schmermund, Axel; et al.
Background: Thoracic aortic calcification (TAC) is associated with cardiovascular (CV) risk factors and prevalent coronary artery disease. We aimed to investigate whether TAC burden is associated with incident myocardial infarction (MI) and all-cause mortality in subjects without known coronary artery disease and to determine its predictive value for these endpoints. Methods: We used longitudinal data from the population-based prospective Heinz Nixdorf Recall Study. TAC and coronary artery calcification (CAC) scores were quantified from non-contrast enhanced electron beam computed tomography. Cox regression analysis was used to determine the association of TAC with incident MI or all-cause mortality, adjusting for CV risk factors and additionally for CAC-score in a separate step. Predictive value of TAC was assessed using Harrell's C index. Results: Overall, 4040 participants without known coronary artery disease (59.4 years, 47% male) were included in this analysis. During a mean follow-up of 8.0 ± 1.5 years, we observed 136 coronary events and 304 deaths. In subjects with TAC>0 vs TAC = 0, the incidence of nonfatal MI was 4.2% vs 2.0% ( p  < 0.001), and all-cause mortality was 8.9% vs 5.2% ( p  < 0.001). Risks for coronary events and for all-cause mortality increased significantly with increasing TAC-scores ( p  < 0.001). After adjustment for CV risk factors, body mass index (BMI) and CV medication, a unit increase of TAC on a logarithmic scale (log(TAC + 1)) remained independently associated with coronary events (hazard ratio (HR) (95% confidence interval (CI)): 1.06 (1.00–1.14), p  = 0.03) and all-cause mortality (HR 1.06 (1.01–1.12), p  < 0.01). After further adjustment for CAC-score (log(CAC + 1)), hazard ratios were attenuated for both endpoints (coronary events: 0.98 (0.91–1.05), p  = 0.56, all-cause mortality: 1.03 (0.98–1.08), p  = 0.33). When adding log(TAC + 1) to the model containing traditional risk factors and CAC, Harrell's C indices did not increase for coronary events (0.773–0.772, p  = 0.66) or for all-cause mortality (0.741–0.743, p  = 0.49). Conclusion: TAC is associated with incident coronary events and all-cause mortality independent of traditional CV risk factors in the general population. TAC fails to improve event prediction over CAC in both coronary events and all-cause mortality.